Development and validation of the SDLD score: a simplified tool to predict successful endoscopic papillectomy in ampullary lesions - Vu Trung, Kien; Abou-Ali, Einas; Gulla, Aiste; Soares, Kevin; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Halimi, Asif; Masaryk, Viliam; Bruno, Marco J.; Pérez-Cuadrado-Robles, Enrique; Bolm, Louisa; et al. (Gastrointestinal Endoscopy, 2025)
Background and Aims: Endoscopic papillectomy (EP) is the standard treatment for noninvasive ampullary lesions (ALs), whereas advanced cases require surgery. Managing ALs is challenging and may lead to over- or undertreatment. We developed a score to identify the best candidates for endoscopic or surgical treatment. Methods: We analyzed 447 patients who underwent EP. The cohort was randomly split into a training set (n = 325) and validation set (n = 122). Logistic regression identified predictors for incomplete resection (R1), which were incorporated into a 4-item score. Performance was assessed using the area under the receiver-operating characteristic curve (AUROC). Results: Independent predictors for R1 included size ≥30 mm (S), high-grade dysplasia and/or invasive cancer (D), laterally spreading-lesion (L), and bile or pancreatic duct dilation (D), which we named the SDLD score. ALs with 0 to 1 points had the highest complete resection rates (training, 86.0%; validation, 88.5%), whereas ≥2 points significantly increased R1 rates (training, 52.0%; validation, 57.7%; P < .001). The AUROC was 0.792 (training) and 0.708 (validation). Conclusions: The SDLD score predicts R1 in EP and aids in treatment decisions.
CRIS-Team Scopus Importer:2025-08-22

Diabetes in all hospitalized cases in Germany 2015–2019 and impact of the first COVID-19 year 2020 - Auzanneau, Marie; Eckert, Alexander J.; Fritsche, Andreas; Heni, Martin; Icks, Andrea; Mueller-Stierlin, Annabel S.; Dugic, Ana; Risse, Alexander; Lanzinger, Stefanie; Holl, Reinhard W. (Endocrine Connections, 2023)
Objective: To analyze the proportion of diabetes among all hospitalized cases in Germany between 2015 and 2020. Methods: Using the nationwide Diagnosis-Related-Groups statistics, we identified among all inpatient cases aged ≥ 20 years all types of diabetes in the main or secondary diagnoses based on ICD-10 codes, as well all COVID-19 diagnoses for 2020. Results: From 2015 to 2019, the proportion of cases with diabetes among all hospitalizations increased from 18.3% (3.01 of 16.45 million) to 18.5% (3.07 of 16.64 million). Although the total number of hospitalizations decreased in 2020, the proportion of cases with diabetes increased to 18.8% (2.73 of 14.50 million). The proportion of COVID-19 diagnosis was higher in cases with diabetes than in those without in all sex and age subgroups. The relative risk (RR) for a COVID-19 diagnosis in cases with vs without diabetes was highest in age group 40–49 years (RR in females: 1.51; in males: 1.41). Conclusions: The prevalence of diabetes in the hospital is twice as high as the prevalence in the general population and has increased further with the COVID-19 pandemic, underscoring the increased morbidity in this high-risk patient group. This study provides essential information that should help to better estimate the need for diabetological expertise in inpatient care settings.
CRIS-Team Scopus Importer:2023-05-26
Keywords: COVID-19; Diabetes; DRG; hospitalization; inpatient care; trend

Endoscopic papillectomy for ampullary lesions in patients with familial adenomatous polyposis compared with sporadic lesions: a propensity score-matched cohort - Vu Trung, Kien; Abou-Ali, Einas; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Masaryk, Viliam; van der Wiel, Sophia E.; Pérez-Cuadrado-Robles, Enrique; Musquer, Nicolas; Halimi, Asif; Soares, Kevin; Souche, Francois R.; et al. (Endoscopy, 2023)
BACKGROUND: Familial adenomatous polyposis (FAP) is a rare inherited syndrome that predisposes the patient to cancer. Treatment of FAP-related ampullary lesions is challenging and the role of endoscopic papillectomy has not been elucidated. We retrospectively analyzed the outcomes of endoscopic papillectomy in matched cohorts of FAP-related and sporadic ampullary lesions (SALs). METHODS: This retrospective multicenter study included 1422 endoscopic papillectomy procedures. Propensity score matching including age, sex, comorbidity, histologic subtype, and size was performed. Main outcomes were complete resection (R0), technical success, complications, and recurrence. RESULTS: Propensity score matching identified 202 patients (101 FAP, 101 SAL) with comparable baseline characteristics. FAP patients were mainly asymptomatic (79.2 % [95 %CI 71.2-87.3] vs. 46.5 % [95 %CI 36.6-56.4]); P < 0.001). The initial R0 rate was significantly lower in FAP patients (63.4 % [95 %CI 53.8-72.9] vs. 83.2 % [95 %CI 75.8-90.6]; P = 0.001). After repeated interventions (mean 1.30 per patient), R0 was comparable (FAP 93.1 % [95 %CI 88.0-98.1] vs. SAL 97.0 % [95 %CI 93.7-100]; P = 0.19). Adverse events occurred in 28.7 %. Pancreatitis and bleeding were the most common adverse events in both groups. Severe adverse events were rare (3.5 %). Overall, 21 FAP patients (20.8 % [95 %CI 12.7-28.8]) and 16 SAL patients (15.8 % [95 %CI 8.6-23.1]; P = 0.36) had recurrence. Recurrences occurred later in FAP patients (25 [95 %CI 18.3-31.7] vs. 2 [95 %CI CI 0.06-3.9] months). CONCLUSIONS: Endoscopic papillectomy was safe and effective in FAP-related ampullary lesions. Criteria for endoscopic resection of ampullary lesions can be extended to FAP patients. FAP patients have a lifetime risk of relapse even after complete resection, and require long-time surveillance.
CRIS-Team Scopus Importer:2023-08-11

Endoscopic papillectomy for ampullary lesions of minor papilla - Vu Trung, Kien; Heise, Christian; Abou-Ali, Einas; Auriemma, Francesco; Karam, Elias; van der Wiel, Sophia E.; Bruno, Marco J.; Caillol, Fabrice; Giovannini, Marc; Masaryk, Viliam; Will, Uwe; Anderloni, Andrea; et al. (Gastrointestinal Endoscopy, 2024)
Background and Aims: Ampullary lesions (ALs) of the minor duodenal papilla are extremely rare. Endoscopic papillectomy (EP) is a routinely used treatment for AL of the major duodenal papilla, but the role of EP for minor AL has not been accurately studied. Methods: We identified 20 patients with ALs of minor duodenal papilla in the multicentric database from the Endoscopic Papillectomy vs Surgical Ampullectomy vs Pancreatitcoduodenectomy for Ampullary Neoplasm study, which included 1422 EPs. We used propensity score matching (nearest-neighbor method) to match these cases with ALs of the major duodenal papilla based on age, sex, histologic subtype, and size of the lesion in a 1:2 ratio. Cohorts were compared by means of chi-square or Fisher exact test as well as Mann-Whitney U test. Results: Propensity score–based matching identified a cohort of 60 (minor papilla 20, major papilla 40) patients with similar baseline characteristics. The most common histologic subtype of lesions of minor papilla was an ampullary adenoma in 12 patients (3 low-grade dysplasia and 9 high-grade dysplasia). Five patients revealed nonneoplastic lesions. Invasive cancer (T1a), adenomyoma, and neuroendocrine neoplasia were each found in 1 case. The rate of complete resection, en-bloc resection, and recurrences were similar between the groups. There were no severe adverse events after EP of lesions of minor papilla. One patient had delayed bleeding that could be treated by endoscopic hemostasis, and 2 patients showed a recurrence in surveillance endoscopy after a median follow-up of 21 months (interquartile range, 12-50 months). Conclusions: EP is safe and effective in ALs of the minor duodenal papilla. Such lesions could be managed according to guidelines for EP of major duodenal papilla.
CRIS-Team Scopus Importer:2024-03-01

Endoscopic papillectomy for laterally spreading lesions of the papilla: a propensity score-matched analysis - Vu Trung, Kien; Abou-Ali, Einas; Gulla, Aiste; Soares, Kevin; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Halimi, Asif; Masaryk, Viliam; Bruno, Marco J.; Pérez-Cuadrado-Robles, Enrique; Bolm, Louisa; et al. (Endoscopy, 2025)
Background Endoscopic papillectomy is a standard treatment for ampullary lesions, which are typically small and confined to the papillary mound. Laterally spreading lesions (LSLs) of the papilla of Vater are a rare ampullary lesion subtype involving extensive duodenal mucosa. Data on endoscopic papillectomy outcomes for LSLs are limited. This study compared endoscopic papillectomy for ampullary LSLs and non-LSLs in matched cohorts. Methods The ESAP study (Endoscopic papillectomy vs. Surgical Ampullectomy vs. Pancreaticoduodenectomy for ampullary neoplasm) encompassed 1422 endoscopic papillectomies. Propensity score matching used the nearest-neighbor method for age, sex, co-morbidity, and histologic subtype as cofactors. The main outcomes were complete resection (R0), technical success, complications, and recurrences. Results Propensity score-based matching identified 232 patients with ampullary lesions (116 non-LSL, 116 LSL) with comparable baseline characteristics. After first intervention, the R0 resection rate, the primary outcome measure, was significantly lower in the LSL group (54.3% [95%CI 45.3%-63.1%]) vs. 69.0% [95%CI 60.4%-76.6%]). Following repeated endoscopic interventions, technical success was similar in both groups (82.8%). After a 22-month median follow-up, the LSL group had significantly more recurrences (41.3% vs. 15.0%) and lower 1- and 3-year disease-free survival rates (61.1% and 44.0% vs. 86.1% and 81.6%, respectively). Complication rates did not differ significantly between the two groups (LSL 32.8% vs. non-LSL 26.7%). Conclusion LSLs can be safely resected by endoscopic papillectomy, although repeated interventions are necessary to achieve complete resection. The higher risk of recurrence in LSLs necessitates a vigilant surveillance strategy.
CRIS-Team Scopus Importer:2025-11-21

Fructose-induced severe hypertriglyceridemia and diabetes mellitus: a cautionary tale - Dugic, Ana; Kryk, Michael; Mellenthin, Claudia; Braig, Christoph; Catanese, Lorenzo; Petermann, Sandy; Kothmann, Juergen; Mühldorfer, Steffen (Endocrinology, Diabetes and Metabolism Case Reports, 2021)
Drinking fruit juice is an increasingly popular health trend, as it is widely perceived as a source of vitamins and nutrients. However, high fructose load in fruit beverages can have harmful metabolic effects. When consumed in high amounts, fructose is linked with hypertriglyceridemia, fatty liver and insulin resistance. We present an unusual case of a patient with severe asymptomatic hypertriglyceridemia (triglycerides of 9182 mg/dL) and newly diagnosed type 2 diabetes mellitus, who reported a daily intake of 15 L of fruit juice over several weeks before presentation. The patient was referred to our emergency department with blood glucose of 527 mg/dL and glycated hemoglobin (HbA1c) of 17.3%. Interestingly, features of diabetic ketoacidosis or hyperosmolar hyperglycemic state were absent. The patient was overweight with an otherwise unremarkable physical exam. Lipase levels, liver function tests and inflammatory markers were closely monitored and remained unremarkable. The initial therapeutic approach included i.v. volume resuscitation, insulin and heparin. Additionally, plasmapheresis was performed to prevent potentially fatal complications of hypertriglyceridemia. The patient was counseled on balanced nutrition and detrimental effects of fruit beverages. He was discharged home 6 days after admission. At a 2-week follow-up visit, his triglyceride level was 419 mg/dL, total cholesterol was 221 mg/dL and HbA1c was 12.7%. The present case highlights the role of fructose overconsumption as a contributory factor for severe hypertriglyceridemia in a patient with newly diagnosed diabetes. We discuss metabolic effects of uncontrolled fructose ingestion, as well as the interplay of primary and secondary factors, in the pathogenesis of hypertriglyceridemia accompanied by diabetes.
CRIS-Team WoS Importer:2022-02-11

Outcomes of rescue procedures in the management of locally recurrent ampullary tumors: A Pancreas 2000/EPC study - Karam, Elias; Hollenbach, Marcus; Ali, Einas Abou; Auriemma, Francesco; Gulla, Aiste; Heise, Christian; Regner, Sara; Gaujoux, Sébastien; Regimbeau, Jean M.; Kähler, Georg; Seyfried, Steffen; Vaillant, Jean C.; et al. (Surgery, 2023)
Background: Ampullary lesions are rare and can be locally treated either with endoscopic papillectomy or transduodenal surgical ampullectomy. Management of local recurrence after a first-line treatment has been poorly studied. Methods: Patients with a local recurrence of an ampullary lesion initially treated with endoscopic papillectomy or transduodenal surgical ampullectomy were retrospectively included from a multi-institutional database (58 centers) between 2005 and 2018. Results: A total of 103 patients were included, 21 (20.4%) treated with redo endoscopic papillectomy, 14 (13.6%) with transduodenal surgical ampullectomy, and 68 (66%) with pancreaticoduodenectomy. Redo endoscopic papillectomy had low morbidity with 4.8% (n = 1) severe to fatal complications and a R0 rate of 81% (n = 17). Transduodenal surgical ampullectomy and pancreaticoduodenectomy after a first procedure had a higher morbidity with Clavien III and more complications, respectively, 28.6% (n = 4) and 25% (n = 17); R0 resection rates were 85.7% (n = 12) and 92.6% (n = 63), both without statistically significant difference compared to endoscopic papillectomy (P = .1 and 0.2). Pancreaticoduodenectomy had 4.4% (n = 2) mortality. No deaths were registered after transduodenal surgical ampullectomy or endoscopic papillectomy. Recurrences treated with pancreaticoduodenectomy were more likely to be adenocarcinomas (79.4%, n = 54 vs 21.4%, n = 3 for transduodenal surgical ampullectomy and 4.8%, n = 1 for endoscopic papillectomy, P < .0001). Three-year overall survival and disease-free survival were comparable. Conclusion: Endoscopy is appropriate for noninvasive recurrences, with resection rate and survival outcomes comparable to surgery. Surgery applies more to invasive recurrences, with transduodenal surgical ampullectomy rather for carcinoma in situ and early cancers and pancreaticoduodenectomy for more advanced tumors.
CRIS-Team Scopus Importer:2023-01-27

Risk Factors for Pancreatic Cancer in Patients with New-Onset Diabetes: A Systematic Review and Meta-Analysis - Mellenthin, Claudia; Balaban, Vasile Daniel; Dugic, Ana; Cullati, Stephane (Cancers, 2022)
(1) Background: Patients with new-onset diabetes (NOD) are at risk of pancreatic ductal adenocarcinoma (PDAC), but the most relevant additional risk factors and clinical characteristics are not well established. (2) Objectives: To compare the risk for PDAC in NOD patients to persons without diabetes. Identify risk factors of PDAC among NOD patients. (3) Methods: Medline, Embase, and Google Scholar were last searched in June 2022 for observational studies on NOD patients and assessing risk factors for developing PDAC. Data were extracted, and Meta-Analysis was performed. Pooled effect sizes with 95% confidence intervals (CI) were estimated with DerSimonian & Laird random effects models. (4) Findings: Twenty-two studies were included, and 576,210 patients with NOD contributed to the analysis, of which 3560 had PDAC. PDAC cases were older than controls by 6.14 years (CI 3.64–8.65, 11 studies). The highest risk of PDAC involved a family history of PDAC (3.78, CI 2.03–7.05, 4 studies), pancreatitis (5.66, CI 2.75–11.66, 9 studies), cholecystitis (2.5, CI 1.4–4.45, 4 studies), weight loss (2.49, CI 1.47–4.22, 4 studies), and high/rapidly increasing glycemia (2.33, CI 1.85–2.95, 4 studies) leading to more insulin use (4.91, CI 1.62–14.86, 5 studies). Smoking (ES 1.20, CI 1.03–1.41, 9 studies) and alcohol (ES 1.23, CI 1.09–1.38, 9 studies) have a smaller effect. (5) Conclusion: Important risk factors for PDAC among NOD patients are age, family history, and gallstones/pancreatitis. Symptoms are weight loss and rapid increase in glycemia. The identified risk factors could be used to develop a diagnostic model to screen NOD patients.
CRIS-Team Scopus Importer:2022-10-28
Keywords: cancer screening; meta-analysis; new onset diabetes; pancreatic cancer; risk factors

The Clinical Utility of Soluble Serum Biomarkers in Autoimmune Pancreatitis: A Systematic Review - Dugic, Ana; Gil, Cristina Verdejo; Mellenthin, Claudia; Vujasinovic, Miroslav; Löhr, J. Matthias; Mühldorfer, Steffen (Biomedicines, 2022)
Autoimmune pancreatitis (AIP) is a rare etiological type of chronic pancreatitis. The clinical and radiological presentation of AIP often resembles that of pancreatic cancer. Identifying non-invasive markers for their early distinction is of utmost importance to avoid unnecessary surgery or a delay in steroid therapy. Thus, this systematic review was conducted to revisit all current evidence on the clinical utility of different serum biomarkers in diagnosing AIP, distinguishing AIP from pancreatic cancer, and predicting disease course, steroid therapy response, and relapse. A systematic review was performed for articles published up to August 2021 by searching electronic databases such as MEDLINE, Web of Science, and EMBASE. Among 5123 identified records, 92 studies were included in the qualitative synthesis. Apart from immunoglobulin (Ig) G4, which was by far the most studied biomarker, we identified autoantibodies against the following: lactoferrin, carboanhydrase II, plasminogen-binding protein, amylase-α2A, cationic (PRSS1) and anionic (PRSS2) trypsinogens, pancreatic secretory trypsin inhibitor (PSTI/SPINK1), and type IV collagen. The identified novel autoantigens were laminin 511, annexin A11, HSP-10, and prohibitin. Other biomarkers included cytokines, decreased complement levels, circulating immune complexes, N-glycan profile changes, aberrant miRNAs expression, decreased IgA and IgM levels, increased IgE levels and/or peripheral eosinophil count, and changes in apolipoprotein isoforms levels. To our knowledge, this is the first systematic review that addresses biomarkers in AIP. Evolving research has recognized numerous biomarkers that could help elucidate the pathophysiological mechanisms of AIP, bringing us closer to AIP diagnosis and its preoperative distinction from pancreatic cancer.
CRIS-Team Scopus Importer:2022-07-15
Keywords: autoantibody; autoimmune pancreatitis; cytokines; immunoglobulins; soluble biomarkers

UEG position paper: Obesity and digestive health - Burra, Patrizia; Arvanitakis, Marianna; Dias, Jorge Amil; Bretthauer, Michael; Dugic, Ana; Hartmann, Daniel; Michl, Patrick; Seufferlein, Thomas; Torres, Joana; Törnblom, Hans; van Leerdam, Monique E.; Zelber-Sagi, Shira; et al. (United European Gastroenterology Journal, 2022)
CRIS-Team Scopus Importer:2024-12-16